Determinasi Keputusan Pembelian Mie Instan: Perspektif Kualitas Produk, Citra Merek, dan Persepsi Harga - Edy Nursanta; Sevina Eka Putri; Widiyarsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the partial and simultaneous effects of Product Quality, Brand Image, and Price Perception on the Purchase Decision of Mie Sedaap, as well as to identify the most dominant variable influencing it. The analytical method used in this study employs quantitative primary data. The testing stages include validity, reliability, normality, heteroscedasticity, multicollinearity tests, multiple linear regression analysis, coefficient of determination, F-test, and t-test. The data in this study were collected using a questionnaire instrument, with 150 valid respondents successfully obtained. The sampling method used was non-probability sampling with a purposive sampling technique. The statistical analysis was conducted using SPSS version 27. The results indicate that Product Quality, Brand Image, and Price Perception simultaneously affect the Purchase Decision of Mie Sedaap, with an F-statistic value of 34.490. This value is greater than the F-table value of 2.67, with a significance level of 0.000 < 0.05. Meanwhile, the partial test results show that Product Quality has a significant effect, with a t-statistic of 3.316 > 1.976 and a significance value of 0.001 < 0.05. Brand Image also has a significant effect, with a t-statistic of 2.407 > 1.976 and a significance value of 0.017 < 0.05. Price Perception has a partial effect on the Purchase Decision of Mie Sedaap, with a t-statistic of 5.667 > 1.976 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) test shows an Adjusted R Square value of 0.403, indicating that Product Quality, Brand Image, and Price Perception explain 40.3% of the variance in Purchase Decisions, while the remaining 59.7% is influenced by other variables.